Irrigation system salinity management modelling - Aslam, Muhammad; Skogerboe, G.V. (1995)
A salinity management model is developed for analysing an irrigation system (small or large), which consists of a hydro-salinity submodel, a soil moisture chemistry submodel, and a groundwater salinity submodel. The hydro -salinity submodel calculates water and salt budgets for an irrigation system in order to determine the recharge rate into the groundwater reservoir. The soil moisture chemistry submodel predicts soil moisture movement and transport of solutes in the unsaturated soil profile considering the cation exchange, precipitation and dissolution of gypsum and lime in the soil solution. The three-dimensional groundwater salinity submodel predicts the spatial and temporal changes in groundwater salinity, as well as temporal variations in the salinity of pumped water.